Analisa Sistem Informasi Pelayanan Publik Pada Kecamatan Neglasari Kota Tangerang - Arif Marjuki; Turki Salim; Suci Fitriyani Drajat (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2021)
Rapid progress in information technology is increasing year by year. The role of millennials as "Agents of Change" is very influential on changes in information technology in the future. The purpose of this research is to research and make changes from an ongoing system to a system that can be more controlled, better and more efficient. The problem faced by the current system is that there is a community behavior, namely the lack of human resources. The barcode of the residence certificate has not been updated with Family Cards, old ID cards, lack of reporting of deaths and births, people prefer manuals, limited officers and many who have not used technology. Then, socialization needs to be further improved. The solution that can be proposed is that the website that is created already has a menu for socialization to residents of Neglasari District, Tangerang City to make it easier for residents to make ID cards and Family Cards. The results of the research that have been researched are that with the proposed system, the public can make it easier, safer and free of charge in submitting online.